Valorization of Vegetable Fresh-Processing Residues as Functional Powdered Ingredients. A Review on the Potential Impact of Pretreatments and Drying Methods on Bioactive Compounds and Their Bioaccessibility - Ramírez-Pulido, Bibiana; Bas-Bellver, Claudia; Betoret, Noelia; Barrera, Cristina; Seguí, Lucía (Frontiers in Sustainable Food Systems, 2021)
Food waste is a worldwide concern as it represents a constant threat to the environment and a serious operational problem for the food industry. The by-products of fruits and vegetables being a valuable source of bioactive compounds have the potential to be reused and reintroduced in the agri-food chain. This circular approach contributes to a sustainable production system. In this context, a collaborative project with the primary sector for the integral valorization of the waste generated in the fresh-processing vegetable lines of an agricultural cooperative is currently being developed, particularly focused on cabbage, carrot, celery, and leek. The objective of this project is to transform vegetable wastes into functional powdered ingredients and be able to use them in food formulations in order to improve the nutritional profile of foods, contributing to the development of sustainable healthy diets. Through an exhaustive bibliographic review, this research studies the influence of pretreatments, drying and in vitro digestion on the bioactive compounds of vegetable residues, with the aim of identifying the appropriate production parameters to achieve an adequate functional and physicochemical profile of the final powders.